An Analysis of Code-Mixing in Web Series: My Nerd Girl Season 1 - Setiawati, Elis; Sholeha, Iqlima; Juli Kristiani, Helpmi; Andini, Jelya; Munari, Muhammad (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
This study investigates how code-mixing is employed in the first season of the Indonesian web series My Nerd Girl, focusing on its linguistic forms, communicative functions, and specific types. In a multilingual setting like Indonesia, the blending of Indonesian and English frequently appears in everyday discourse, and this series provides a relevant representation of such practices. The main objective of this research is to describe how code- mixing occurs in the characters’ dialogues and to explain the roles it plays within the narrative. A qualitative descriptive design was applied, and Muysken’s (2000) typology was used to classify the linguistic patterns observed. Through this framework, three major types of code- mixing were identified: insertion, alternation, and congruent lexicalization. The analysis shows that insertion predominantly appears in the form of English nouns, adjectives, and short expressions that are embedded into Indonesian clauses to create emphasis or introduce a contemporary tone. Alternation surfaces when speakers shift between the two languages across phrases or clauses, often marking emotional shifts, relational positioning, or stylistic variation. Congruent lexicalization emerges when Indonesian and English elements share the same syntactic structure, reflecting the fluid bilingual practices commonly found among urban youth. Overall, the results indicate that code-mixing in My Nerd Girl functions as both a sociolinguistic feature and a narrative technique. Its strategic use supports character development, mirrors real bilingual communication, and enhances the series’ appeal to contemporary audiences.